Revisiting the type of Cespitularia stolonifera Gohar, 1938 leads to the description of a new genus and a species of the family Xeniidae (Octocorallia, Alcyonacea) - Benayahu, Yehuda; Ofwegen, Leen P. Van; Allais, J. P. Ruiz; Mcfadden, Catherine S. (Zootaxa, 2021)
Because of the problematical identity and status of the type of the xeniid soft coral genus Cespitularia Milne-Edwards & Haime, 1850, the species C. stolonifera Gohar, 1938 is revised. Examination of the type colonies has led to the establishment of the new genus Unomia gen. n. which is described and depicted. This genus features a stalk, commonly divided into branches featuring a diffuse polypiferous part consisting of distal clustered polyps and proximal individual ones on the stalk or the basal membranous part of the colonies. The sclerites are ellipsoid platelets composed of dendritic calcite rods whose tips are distinct on the surface of the platelets. Freshly collected material from Venezuelan reefs where the species is invasive was subjected to molecular phylogenetic analysis, the results of which substantiate the taxonomic assignment of the new genus under U. stolonifera comb. n. A new species, U. complanatis, from Japan and Green Island (Taiwan) is described and further illustrates the extent of the interspecific morphological variation within the genus. The results reveal that the biogeographic distribution of Unomia gen. n. includes Pacific Ocean reefs in addition to the previously reported invaded Caribbean reefs.